A mulher presa, sonhos e frustrações: a escola no sistema carcerário - Oliveira, Maria Júlia Silva de (2010)
This work have as object of study women inserted in the Penitentiary System, specifically those whom have studied at Penitenciária Feminina da Capital (Capital Female Penitentiary) schools and Penitenciária Feminina do Butantã (Butantã Female Penitentiary, semi-open prison). The basic objective is to verify the importance of formal and non-formal education of the Penitentiary System School for women, also, as results achieved by them show, measured social inclusion, interaction with the world of regular work and the evolution of relative aspects to recover citizenship post detention. In other words, analyze how these ex-students conquered the knowledge made available by education while in a troublesome environment. The results achieved allow us to affirm that formal Education, just like the non-formal, is a irreplaceble pillar on raising self-esteem, social and professional inclusion of those people that are, or were, prived of liberty, by this argument, earner of greater visibility and effort by the State to make available more acceptable public policies, allowing further interaction among the incarcerated community, managers of detention centers, teachers, school and society.